Regulating innovative health technologies: dialectics, dialogics, and the case of faecal microbiota transplants. Issue 2 (2nd July 2020) - Kaldor, Jenny; Eckstein, Lisa; Nicol, Dianne; Stewart, Cameron
ABSTRACT: This paper interrogates the common characterisation of innovative health technologies 'leading', while law and regulation 'lag' behind. We analysed the case of faecal microbiota transplants (FMT), an innovative procedure whose regulatory status remains in flux worldwide. We searched the literature for papers that described the regulation of FMT, and coded these according to a simple analytic framework. We identified 21 relevant papers. To date, no jurisdiction has implemented FMT-specific regulation. Instead, FMT is dealt with under a range of approaches, which include fitting it within existing regulation, and the use of 'soft' law. We found that metaphor, or argument by analogy, played a central role in delineating the potential regulatory options. We also found the relationship between innovation and regulation to be more 'dialogic' than oppositional, dialectical, or akin to a race. These findings underscore the importance of case-by-case investigation to determine the applicability of general narratives about law and regulation to specific instances of innovative technologies.